A RARE CASE OF DYSTOCIA IN A BITCH DUE TO FETAL CERVICOTHORACIC HEMATOMA ALONG WITH AMELIA OF HIND LIMBS - HONPARKHE, M; MALIK, ASLOOB AHMAD; GHUMAN, S P S; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia in a bitch due to cervico-thoracic hematoma along with absence of hind limbs in pup is reported.